Difficulties Faced by Second Language Learners in Using Collocation - Sarah Nazar Kadhem; Fatima Shawqi Ismail (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This paper reviews the challenges encountered by second language learners in the acquisition and utilization of collocations, which are crucial aspects of proficient language use. Collocations refer to the habitual pairing or grouping of words that occur together frequently in natural language. The research synthesizes findings from various studies conducted in the field, highlighting common difficulties experienced by learners across different proficiency levels and linguistic backgrounds. Key factors contributing to these challenges include differences in first language structures, inadequate exposure to authentic language use, limited awareness of collocational patterns, and difficulties in achieving native-like fluency. Additionally, pedagogical implications and effective instructional strategies for enhancing collocational competence are discussed, is to inform language instructors and curriculum developers in building more targeted and effective language learning materials and activities.This research is divided into three sections; section one presents the preliminaries of the study. Section two explains the meaning, types, characteristics, and importance of the study. Section three will apply a test of collocation on the 4th stage of the college to know their weakness points in collocation. Finally, the conclusion is the research.